Genomic evidence of an ancient inland temperate rainforest in the Pacific Northwest of North America. Issue 10 (9th April 2022) - Ruffley, Megan; Smith, Megan L.; Espíndola, Anahí; Turck, Daniel F.; Mitchell, Niels; Carstens, Bryan; Sullivan, Jack; Tank, David C.
Abstract: The disjunct temperate rainforests of the Pacific Northwest of North America (PNW) are characterized by late‐successional dominant tree species Thuja plicata (western redcedar) and Tsuga heterophylla (western hemlock). The demographic histories of these species, along with the PNW rainforest ecosystem in its entirety, have been heavily impacted by geological and climatic changes the PNW has experienced over the last 5 million years, including mountain orogeny and repeated Pleistocene glaciations. These environmental events have ultimately shaped the history of these species, with inland populations potentially being extirpated during the Pleistocene glaciations. Here, we collect genomic data for both species across their ranges to test multiple demographic models, each reflecting a different phylogeographical hypothesis on how the ecosystem‐dominating species may have responded to dramatic climatic change. Our results indicate that inland and coastal populations in both species diverged 2.5 million years ago in the early Pleistocene and experienced decreases in population size during glacial cycles, with subsequent population expansion. Importantly, we found evidence for gene flow between coastal and inland populations during the mid‐Holocene. It is likely that intermittent migration in these species during this time has prevented allopatric speciation via genetic drift alone. In conclusion, our results from combining genomic data and demographic inference procedures establish that populations of the ecosystem dominants Thuja plicata and Tsuga heterophylla persisted in refugia located in both the coastal and inland regions of the PNW throughout the Pleistocene, with populations expanding and contracting in response to glacial cycles with occasional gene flow.